PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS ANGGOTA KSP SEKAWAN BOJA ( Studi Pada Anggota Koperasi ) - Faisal Bintang, 14.05.51.0096; Soliha, Euis (Students' Journal of Economic and Management, 2019)
This study aims to empirically examine the Effect of Service Quality, Product Quality on Satisfaction and Its Impact on KSP Sekawan Boja Customer Loyalty (Study on Savings Customers). This analysis uses independent variables namely Service Quality and Product Quality. The dependent variable is Customer Satisfaction and Loyalty.The sample of this study is the KSP savings customer Sekawan Boja. The sample is carried out by purposive sampling. Data collection was conducted with a questionnaire distributed directly to a sample of 100 questionnaires. Statistical methods use multiple linear regression analysis, by testing the statistical test hypothesis t.The results of this study indicate that service quality positively significantly affects customer satisfaction, product quality positively significantly affects customer satisfaction, and customer satisfaction positively significantly affects customer loyalty.